UJI EFEKTIFITAS METODE FUZZY LOGIC MAMDANI PADA PENERIMAAN BEASISWA BANTUAN MENGGUNAKAN MATLAB - Febie Elfaladonna; Indra Griha Tofik Isa (Prahasta Publisher, 2022)
One of the supporters in creating an even educational climate is the existence of scholarships. In general, scholarships in the form of financial assistance intended for the community of higher education, both lecturers, teachers, students and students. In the awarding of scholarships, some findings were obtained, including not being on target which caused the scholarship assistance to be ineffective. One solution in determining the acceptance of scholarships is the existence of a system that is integrated with decision-making methods. Fuzzy logic mamdani becomes one of the recommendation methods that can be implemented in decision making. So the formulation of the problem of this research is (1) How is the implementation of fuzzy logic mamdani methods to the decision-making system of receiving aid scholarships?; (2) How effective fuzzy logic methods mamdani to the decision-making system of aid scholarship. The scope of the research is (1) The method of inference with Fuzzy Logic Mamdani; (2) The tools used are Matlab version R2021b; (3) The input variable criteria consist of parental income, achievement (academic and non-academic) and average grades throughout the semester; (4) The variable output criterion is the amount of the scholarship. The final results of the study resulted in the calculation of the effectiveness of the Fuzzy Mamdanil Method of more than 50%, so that the fuzzy mamdani method can be recommended as an alternative in the decision-making method determining the amount of acceptance of aid scholarships.